Perencanaan Strategis Sistem Informasi PT. Al-Yaubi Menggunakan Metode Ward Peppard - Alif Elmusa Widinandra; Asif Faroqi; Eristya Maya Safitri (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Strategic planning is the embodiment of a strategy in a plan that involves making strategies, directions, decisions, and effective management of the two processes so that the strategy can be implemented. One form of strategic planning is information systems strategic planning. PT. Al-Yaubi is an organization/company engaged in the sale of domestic tickets. As a company engaged in the sale of tickets from various transportation. Information systems and information technology at PT Al-Yaubi have not been fully operational and used optimally, where there are still several business processes that are still being done manually. Strategic planning information system method proposed by Ward Peppard is used in research by producing Ward and Peppard portfolios that are in line with the vision and mission. The results of the information system strategic planning that has been carried out which includes Information System business strategy, IT strategy and Information System/Information Technology management strategy. This Information System strategy determines the Information System application portfolio of PT. Al-Yaubi which must be built.Keywords: Information Technology; Information Systems; Strategic Planning AbstrakPerencanaan strategis merupakan perwujudan suatu strategi dalam suatu rencana yang melibatkan pembuatan strategi, arahan, keputusan, dan pengelolaan yang efektif dari kedua proses tersebut agar strategi dapat dijalankan, salah satu bentuk perencanaan strategis adalah perencanaan strategis sistem informasi. PT. Al-Yaubi adalah sebuah organisasi/perusahaan yang bergerak dibidang penjualan tiket domestik. Sebagai perusahaan yang bergerak dibidang penjualan tiket dari berbagai transportasi. Sistem informasi dan Teknologi informasi pada PT Al-Yaubi belum sepenuhnya berjalan menggunakan system informasi dan teknologi informasi, dimana tetap ada beberapa aktivitas bisnis yang tetap dikerjakan dengan tangan. Hasil perencanaanii strategisiii sistema informasit yang telaho dilakukanti yang mencakup strategii bisnisi Sistem Informasi, strategii untuk teknologii informasii dani jugai strategii untuk manajemen iSistem Informasi/Teknologi Informasi. Hasil tersebut yangii menentukan portofolio aplikasi           PT. Al-Yaubi yang harus dibangun.